(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the problem of developing epistemological problems of language and the science of language in the framework of cognitive linguistics. Cognitive linguistics is considered in close connection with the problem field of scientific identification of the phenomenon of language within the framework of pragmalinguistics.